Respuesta :
a) To find x for f(x) = 0, substitute the given information and solve for x.
.. f(x) = 0 = -0.5x +2.5
.. 0.5x = 2.5 . . . . . . . . . . add 0.5x
.. x = 2.5/0.5 = 5 . . . . . . divide by the coefficient of x
f(5) = -0.5*5 +2.5 = 0
b) f(0) = -0.5*0 +2.5 = 2.5
.. f(x) = 0 = -0.5x +2.5
.. 0.5x = 2.5 . . . . . . . . . . add 0.5x
.. x = 2.5/0.5 = 5 . . . . . . divide by the coefficient of x
f(5) = -0.5*5 +2.5 = 0
b) f(0) = -0.5*0 +2.5 = 2.5
Answer:
1. [tex]x=5, f(x)=0[/tex], [tex]f(5)=0[/tex]
2. [tex]x=0, f(x)=2.5[/tex], [tex]f(0)=2.5[/tex]
Step-by-step explanation:
We have the expression: [tex]f(x)=-0.5x+2.5[/tex]
First we are going to calculate [tex]f(x)=0[/tex] this is:
[tex]f(x)=0\\-0.5x+2.5=0[/tex]
We can subtract 2.5 from both sides of the equation,
[tex]-0.5x+2.5=0\\-0.5x+2.5-2.5=-2.5\\-0.5x=-2.5[/tex]
Now, divide both sides in (-0.5),
[tex]-0.5x=-2.5\\\\\frac{-0.5x}{-0.5}=\frac{-2.5}{-0.5}\\\\x=5[/tex]
This means that for
[tex]x=5, f(x)=0[/tex]
or you can rewrite it as:
[tex]f(5)=0[/tex]
Now we have to calculate [tex]f(0)[/tex], this means that we have to replace [tex]f(x)[/tex] with [tex]x=0[/tex]. This is:
[tex]f(x)=-0.5x+2.5\\f(0)=-0.5(0)+2.5\\f(0)=0+2.5\\f(0)=2.5[/tex]
[tex]x=0, f(x)=2.5[/tex]
or rewrite it as
[tex]f(0)=2.5[/tex]